ANALISIS KINERJA TENAGA PENJUALAN BERDASARKAN GENDER PADA PT. TELKOM INDONESIA WITEL MAGELANG - Hendi Ari Wibowo; Heni Hirawati (Transpublika Publisher, 2022)
This study aims to see whether there are differences in performance between salespeople at PT Telkom Indonesia Witel Magelang from a gender perspective. The population of this study was 306 salespeople consisting of 214 males and 92 females. The analysis of this research is seen from the difference in average, highest sales, and standard deviation of sales for each gender. The results showed that the average sales showed the differences between male and female salespeople. From the highest sales, it shows the dominance of female salespeople from the number of individual sales. The standard deviation describes the distribution of the average sales. This study shows that female salespeople have a more unequal distribution than male salespeople. The dominance of male salespeople in terms of numbers did not make sales performance increase drastically. Female salespeople dominate on average and from maximum sales in a few months. These results indicate that there are differences in performance between male and female salespeople.